2017
DOI: 10.1088/1475-7516/2017/01/044
|View full text |Cite
|
Sign up to set email alerts
|

Inflation in Flatland

Abstract: We investigate the symmetry structure of inflation in 2+1 dimensions. In particular, we show that the asymptotic symmetries of three-dimensional de Sitter space are in one-to-one correspondence with cosmological adiabatic modes for the curvature perturbation. In 2+1 dimensions, the asymptotic symmetry algebra is infinite-dimensional, given by two copies of the Virasoro algebra, and can be traced to the conformal symmetries of the two-dimensional spatial slices of de Sitter. We study the consequences of this in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…As we mentioned at the outset, the subject of asymptotic symmetries has a wide range of applications, and our results give a new perspective on these applications. For example, in cosmology, the change in the curvature perturbation, ζ, produced by an asymptotic symmetry transformation of dS 3 is identified with adiabatic modes of ζ [40]. The relation to the membrane paradigm described in the present paper allows one to interpret the perturbations produced by adiabatic modes as changes in the energy density of the boundary fluid as observed by a null observer (c.f.…”
Section: Discussionmentioning
confidence: 75%
“…As we mentioned at the outset, the subject of asymptotic symmetries has a wide range of applications, and our results give a new perspective on these applications. For example, in cosmology, the change in the curvature perturbation, ζ, produced by an asymptotic symmetry transformation of dS 3 is identified with adiabatic modes of ζ [40]. The relation to the membrane paradigm described in the present paper allows one to interpret the perturbations produced by adiabatic modes as changes in the energy density of the boundary fluid as observed by a null observer (c.f.…”
Section: Discussionmentioning
confidence: 75%
“…There exist both scalar consistency relations relating the squeezed limit of the (n+1)‐point correlators to the n ‐point correlators of scalar perturbations and tensor consistency relations involving tensor and scalar modes (see also ). Recently, it has been shown that the consistency relations are in close connection with the asymptotic symmetries of de Sitter space since soft degrees of freedom produced by the expansion of de Sitter can be interpreted as the Nambu‐Goldstone bosons of spontaneously broken asymptotic symmetries of the de Sitter spacetime.…”
Section: Consistency Relations From the Ds/cft3 Correspondence Radiamentioning
confidence: 99%
“…Bulk fields ϕ(x,η) evolving in four‐dimensional de Sitter spacetime and behaving near the boundary η=0 (η being the conformal time) as ϕfalse(truex,ηfalse)(η)normalΔϕfalse(truexfalse) correspond on the three‐dimensional space, where the symmetry is CFT 3 , to a field of conformal weight h=Δ3. Correlators of fields excited during a de Sitter phase are therefore expected to be constrained by conformal invariance and the literature on this topic is rich and diverse . In particular, much attention has been devoted to the relation among the consistency relations, soft theorems and the asymptotic symmetries of de Sitter which transform asymptotic vacua to new physically inequivalent vacua by generating long perturbation modes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A deep connection between these soft theorems and asymptotic symmetries of asymptotically-flat spaces has been suggested [19][20][21][22][23][24][25][26]. In a similar way, cosmological soft theorems are related to the asymptotic symmetries of cosmological spacetimes [27][28][29].…”
Section: Introductionmentioning
confidence: 99%